Fatores associados e perfil de tentativas de suicídio por intoxicação - Luciene Oliveira Rocha Lopes (2021)
Suicide is a serious public health problem and presents itself as a complex phenomenon involving biological, social, psychological and cultural factors. Identifying and acting on risk factors for suicide is a strategy for prevention within the scope of public health. Considering that the presence of these factors can present differences between populations, this Dissertation seeks to identify and analyze the risk factors in specific samples and thus contribute to the promotion of preventive actions. The results are reported through two articles. The first study is a systematic review of the specific literature on these factors for attempts and deaths by suicide in Brazil. Of 1265 articles selected according to the defined descriptors, 50 met the eligibility criteria and were analyzed. The work synthesizes the theme in the national context. The second study is an analysis of drugs and other substances used in suicide attempts by intoxication in Brazil. To develop it, medical records and a database from the psychology service of an emergency hospital in Belo Horizonte, Minas Gerais, Brazil, were used. Out of the total of 2088 records of attempts attended in the period from January 2016 to July 2019, intoxications represent 66.9%. Among the drugs present in the attempts, 61.1% have restricted sales, with prescription retention. Therefore, this Dissertation provides an overview of the risk factors associated with suicide in the Brazilian context, with a focus on intoxications. The need to implement policies that can improve the distribution of medicines among the different dispensing systems is highlighted, in addition to promoting exclusive health services for the care of individuals with suicidal behavior and also their families, in order to collaborate with psychoeducation actions in relation to the risks that involve access to the medicines used in the treatments.